Open cholecystectomy of choice Personal series of 2,112 consecutive cases - Estefan, Alberto; Grezzi, Roberto; Montano, Daniel; Lagos, Fernando; Fernández, Gonzalo; Bruno, Gerardo (Cirugía del Uruguay, 1995)
This paper presents the analysis of a prospective series of 2112 open e/ective cholecystectomies carried out by a single surgeon. Dominan/ etiology was ga/1-bladder lithiasis (96,6%). Ga/1-bladder cancer which had been unsuspected in the pre-operative appeared in 0,8% of the cases of chronic lithiasis cholecysthopathies and in 10,4% of adenomatous polyps. Unsuspected biliar and extrabi/iar procedures were carried out in 3,2% and O, l% respective/y There was 5% global mortality; 3% due to biliar causes and 2, 7% to extra biliar ones. There was 0% mortaliy.